Borelijski limfocitom pri otrocih v Sloveniji - demografske, klinične in laboratorijske značilnosti - Vuković, Klavdija (Medicinski razgledi, 2010)
Backgrounds. Lyme borreliosis is a disease which affects many organ systems. It is transmitted by ticks and caused by the bacteria Borrelia burgdorferi sensu lato. Borreliallymphocytoma is a dinical sign of early localized Lyme borreliosis in children. Methods. The dinical study was retrospective. It induded 45 patients who were treated at the Department of Infectious Diseases,University Medical Centre, Ljubljana, Slovenia, from 1 January 2001 to 31 December 2007. The diagnosis ofborreliallymphocytoma was based on the Centers for Disease Control and Prevention criteria for the diagnosis of Lyme borreliosis in children. The basic demographic data and data about the course of the disease were collected using a questionnaire. A group of 42 patients who fulfilled the inclusion criteria was enrolled and included 18 females and 24 males. Results. The medium age of the patients was 5 years. 19% of the patients had had a tick bite. 97.6% of the patients had solitary borreliallymphocytoma. B. burgdorjeri sensu stricto was isolated in one patient's blood. One of the female patients had borreliallymphocytoma, erythema migrans and meningitis simultaneously. Three patients with borrelial lymphocytoma were hospitalized. Conclusions. In children, borreliallymphocytoma appears seasonally, mostly in June. In the majority of children, it appears on the earlobe. For most children, it involves an easy initial disease, but more than half of the cases have associated local and/ orgeneral symptoms. The diagnosis of Lyme borreliosis is confirmed in only onethird of children with borreliallymphocytoma. More than a third of childrenalso have specific antibodies against the borrelias causing Lyme borreliosis, but in the blood of children with borreliallymphocytoma the presence of the latter is very rare.
Keywords: Lyme Disease; Psevdolimfom; Diagnosis; Eritem kronični, migracijski; Drug Therapy; Protitelesa bakterijska; Pseudolymphoma; Otrok; Borrelia Burgdorferi; Letni časi; Antibodies, Bacterial; Lyme borelioza; limfocitom; Erythema Chronicum Migrans; Child; otroci; Seasons; Lymska bolezen